Historical Monuments in Uzbekistan (Journal of Pedagogical Inventions and Practices, 2023)
This article delves into the rich historical heritage of Uzbekistan, a Central Asian country known for its remarkable monuments that span thousands of years. The author explores the captivating historical sites in Uzbekistan's prominent cities like Samarkand, Bukhara, and Khiva, highlighting their significance and the cultural wealth they represent